2015
DOI: 10.1002/mc.22405
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal growth factor receptor derived peptide vaccination to prevent lung adenocarcinoma formation: An in vivo study in a murine model of EGFR mutant lung cancer

Abstract: The ability to prevent disease is the holy grail of medicine. For decades, efforts have been made to extend the successes seen with vaccination against infectious diseases to cancer. In some instances, preventive vaccination against viruses (prototypically HPV) has successfully prevented tumorigenesis and will make a major impact on public health in the decades to come. However, the majority of cancers that arise are a result of genetic mutation within the host, or non-viral environmental exposures. We present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 22 publications
0
30
0
Order By: Relevance
“…The same group has tested in mouse models the ability of vaccines based on non-mutated tumor antigens to prevent cancer. They showed that a multi-antigen vaccine that included Neu, IGFBP2 and IGF-IR could prevent breast cancer development in two different transgenic mouse models even in mice that already had premalignant lesions [31]. This report also showed that a multi-antigen vaccine was more effective than a single antigen vaccine, and that the vaccine could be combined with some chemopreventative agents resulting in increased efficacy of both.…”
Section: Candidate Antigens For Preventative Vaccinesmentioning
confidence: 99%
“…The same group has tested in mouse models the ability of vaccines based on non-mutated tumor antigens to prevent cancer. They showed that a multi-antigen vaccine that included Neu, IGFBP2 and IGF-IR could prevent breast cancer development in two different transgenic mouse models even in mice that already had premalignant lesions [31]. This report also showed that a multi-antigen vaccine was more effective than a single antigen vaccine, and that the vaccine could be combined with some chemopreventative agents resulting in increased efficacy of both.…”
Section: Candidate Antigens For Preventative Vaccinesmentioning
confidence: 99%
“…In another study researchers found that a multi-partite vaccine targeting three antigens on pre-invasive breast disease (Neu, IGFBP2, IGF-IR) could prevent breast cancer in a spontaneous mouse tumor model in which mice were treated after developing premalignant lesions (Disis et al, 2013). Other pre-clinical studies in mice with premalignant lesions have shown that common oncogene mutations that appear early and drive cancer formation could perhaps also be targeted by vaccines in animals including H-ras in carcinogen-induced tumors and EGFR in a lung cancer model (Ebben, Lubet, Gad, Disis, & You, 2016; Nasti et al, 2015). These common oncogenes in addition to others such as K-ras and p53 have been tested in therapeutic vaccines with limited efficacy but warrant further investigation as prophylactic vaccines (Carbone et al, 2005).…”
Section: Prophylactic Cancer Vaccinesmentioning
confidence: 99%
“…Pre-clinical studies in mice engineered to develop spontaneous tumors show that such lesions either do not develop in vaccinated mice or do not progress to cancer (P. L. Beatty, Narayanan, Gariepy, Ranganathan, & Finn, 2010; Ebben et al, 2016). The increasing focus on early detection of cancer, including pre-malignant lesions, as well as identifying genetic and behavioral risk factors for cancer, can define candidate patient populations for prophylactic vaccination.…”
Section: Prophylactic Cancer Vaccinesmentioning
confidence: 99%
“…Although more complex and recent than the development of vaccines against foreign pathogen-associated targets (e.g., hepatitis B), vaccines against the less-immunogenic genetic drivers and other tumor antigens are showing promise in preclinical prevention models (e.g., KRAS in pancreas models; activating EGFR mutations in lung adenocarcinoma [64, 65]) and have now entered early phase clinical trials (e.g., HER2, MUC1). This focus is very timely, as evidenced by a major new initiative by Cancer Research UK, which recently issued a ÂŁ20M Grand Challenge that includes a charge to develop vaccines to prevent non-viral cancers (66).…”
Section: Immunopreventionmentioning
confidence: 99%